China’s belt and road initiative : a perception survey of Asian opinion leaders - Rana, Pradumna Bickram (Nanyang Technological University, 2020)
The Belt and Road Initiative (BRI), officially unveiled in 2013, is China’s landmark foreign and economic policy initiative to achieve improved connectivity, regional cooperation, and economic development on a trans-continental scale. China has promoted the BRI as a cooperative initiative that will lead to a win-win situation for both China and BRI partner countries. However, there are many different views and pushbacks against the BRI and suspicions of China’s underlying intentions. Impacts of the BRI can be assessed either through a model-based quantitative study or through a broadly representative survey. Our paper used the latter approach as we were not aware of any such study in the past. We implemented an online survey from 20 June to 19 July 2019 which over 1,200 Asian opinion leaders responded to. Asian opinion leaders were defined as policy makers, academics, businesses, and media practitioners from 26 Asian countries that have signed a BRI agreement with China. Stakeholders’ perspectives on the following issues were solicited: (i) why China might have been interested in launching the BRI; (ii) perceived benefits and risks to countries participating in the BRI; and (iii) policies that the stakeholders would like to recommend both to China and their own governments. Though mixed views on the specifics of the BRI emerged, respondents generally felt that the BRI was a positive development facilitating international economic cooperation and development. The recommendations of this survey should be of some use in making the BRI a truly win-win initiative for all.